Strategic Bidding of Electric Power Generating Companies: Evidence from the Australian National Energy Market - Mardi Dungey; Ali Ghahremanlou; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2017)
We extend existing theoretical frameworks describing electricity markets where each generator provides a Market Operator (MO) with a supply schedule in advance. The MO combines these with demand forecasts to produce equilibrium prices and instructs firms on their dispatch. We incorporate the possibility that generating firms may rebid (or revise) their supply schedule prior to dispatch - an important feature of markets in many countries which has not previously been included in theoretical models. We show that a dominant firm can gain substantially by manipulating its bids, and take advantage of the opportunity to submit rebids. In the Australian National Energy Market (NEM) where settlement prices are an average of six dispatch prices, it can, for example, withhold capacity at lower prices for the first bid in a period, creating a price hike, and then add capacity at lower prices to ensure dispatch. Using data from the Australian NEM we provide the first empirical evidence consistent with the hypothesized theoretical behaviour in the observed data.
Keywords: Q41; D43; D23; 330; electricity markets; Australia; rebidding